2018
DOI: 10.1016/j.bja.2018.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-tagged near-infrared spectroscopy does not disclose absent cerebral circulation in brain-dead adults

Abstract: In brain-dead patients, where CBF is absent, the UT-NIRS findings can indicate an apparently perfused brain. This might reflect an insufficient separation of signals from extra-cranial structures from a genuine appraisal of cerebral perfusion. For non-invasive assessment of CBF-related parameters, the near-infrared spectroscopy still needs substantial improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…The work by Caccioppola and colleagues 10 forces us to reexamine the much broader and important question of the overall value of NIRS itself. How should we treat parameters obtained with NIRS devices?…”
mentioning
confidence: 99%
“…The work by Caccioppola and colleagues 10 forces us to reexamine the much broader and important question of the overall value of NIRS itself. How should we treat parameters obtained with NIRS devices?…”
mentioning
confidence: 99%
“…This explanation was confirmed in a similar study, which also showed a concomitant decrease in rSO 2 with the SpO 2 after discontinuation of mechanical ventilation [40]. Ultrasound-tagged near-infrared spectroscopy (UT-NIRS) was also unable to differentiate signals from extracranial structures [41]. This explanation may be helpful in our case, as the patient had a SpO 2 of approximately 75% during extracorporeal circulation and after its discontinuation, when the NIRS value was still 68%, suggesting that some residual perfusion was maintained in cerebral circulation or that there was no cerebral circulation, and the NIRS values originated solely from extracerebral tissue.…”
Section: Discussionmentioning
confidence: 86%
“…Despite the limitations of the use of NIRS in situations where there may be brain death [41], Weigl et al recently reported a promising technique for the confirmation of cerebral circulation cessation using bolus tracking of an optical contrast agent, indocyanine green, and time-resolved NIRS [42]. As this case report has shown, NIRS is a promising method that opens a new era of research in the assessment of the cerebral circulation in critical situations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nature of this association is not completely clear. In fact, since NIRS signals can be contaminated from extracerebral circulation [12], rSO 2 values during CPR may reflect whole-body rather than brain perfusion. In addition, patients who achieve ROSC usually show higher rSO 2 values from the beginning of the resuscitation attempt [2], so that it is not clear whether a higher rSO 2 in these patients reflects more effective CPR or, instead, other favourable factors, such as witnessed status or a shorter no-flow time.…”
Section: Current Limitations and Future Perspectivesmentioning
confidence: 99%